The effect of plastic flow in the neck on the scale levels of fracture in polycrystals. Experiment and modeling; Physical mesomechanics; Vol. 14, iss. 1-2 - Panin V. E. Viktor Evgenyevich; Balokhonov R. R. Ruslan Revovich; Derevyagina L. S.; Romanova V. A. (2011, 2011)
Title screen